Analisis Dampak Perubahan Struktur Modal dan Kebijakan Dividen terhadap Biaya Modal pada PT Jasa Marga (Persero) - Budi gautama Siregar; Muhammad Salman; Aswadi Lubis (Jurnal Penelitian Ekonomi Akuntansi, 2025)
This study investigates the relationship between capital structure and dividend policy on the cost of capital at PT Jasa Marga (Persero) Tbk by utilizing quarterly financial data from 2017 to 2024. Capital structure is measured by the Debt to Equity Ratio (DER), dividend policy is represented by the Dividend Payout Ratio (DPR), while the cost of capital is calculated using the Weighted Average Cost of Capital (WACC) approach. PT Jasa Marga was selected as the research object due to its characteristics as a state-owned enterprise (SOE) in the infrastructure sector, which is capital-intensive, long-term oriented, and plays a strategic role in national development. These characteristics make funding decisions and dividend policies highly influential in determining the efficiency of the company’s cost of capital. The research methodology employs a quantitative approach with multiple linear regression analysis. To ensure the validity of the model, several classical assumption tests were conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. An F-test was used to examine the simultaneous influence of the independent variables on the cost of capital, while t-tests were applied to assess the partial effects of each independent variable. This approach provides a comprehensive understanding of the extent to which capital structure and dividend policy contribute to determining the company’s cost of capital. The findings reveal that both capital structure and dividend policy significantly affect the cost of capital at PT Jasa Marga. An increase in DER was found to raise WACC, consistent with the Trade-Off Theory, which emphasizes the balance between tax benefits from debt and the risk of financial distress. Similarly, a higher DPR increases the cost of capital due to reduced retained earnings and greater reliance on external financing. These results highlight that funding strategies and dividend policies in state-owned infrastructure enterprises must be carefully managed to maintain cost efficiency. Academically, this research enriches the literature on the interplay between internal financial policies and cost of capital, while practically, it offers recommendations for managers and policymakers to design more sustainable financing and dividend strategies in support of long-term infrastructure development.